The Impact of ESG Performance on Firm Value: A Study of High and Low Profile Industries in Southeast Asia - Utami, Martiana Riawati; Naufal Afif (Journal of Economics, Business, and Government Challenges, 2025)
The objective of this study is to gather empirical evidence on the relationship between environmental, social and governance performance (ESG performance) and firm value. The study also aims to identify any differences in ESG performance on firm value between high-profile and low-profile industry types. The research sample has been divided based on the type of high-profile and low-profile industry, in order to ascertain the relationship between ESG performance and firm value, with the aim of identifying any differentiating variables. The study utilises a sample comprising companies listed on the Stock Exchange of Thailand, Bursa Malaysia, Singapore Exchange, Philippine Exchange and Indonesia Stock Exchange between 2014 and 2019. The sample was selected using the purposive sampling method. The data analysis employs panel data regression analysis using the Generalised Least Squares (GLS) method. The findings of this study demonstrate that ESG performance has a positive impact on firm value. Furthermore, the ESG performance of companies in the high-profile industry type has the potential to influence the growth of firm value. This research offers insights that can inform the decision-making processes of companies seeking to implement sustainability-related programmes and operational mechanisms through ESG performance. Additionally, it provides a valuable resource for investors considering sustainability information when making investment decisions.